The environmental opportunity cost of using renewable energy for carbon capture and utilization for methanol production. (1st December 2020) - Ravikumar, Dwarakanath; Keoleian, Gregory; Miller, Shelie
Graphical abstract: Highlights: CO2 impact of using renewable energy (RE) to produce MeOH from CO2 quantified. Three sources of electricity and CO2 emissions accounted for. RE on grid versus RE for producing MeOH from CO2 accounted for. RE on the grid avoids greater CO2 than RE for producing MeOH from CO2 . Use RE to produce MeOH from CO2 only if grid intensity is below 67 gCO2 /kWh Abstract: Carbon capture and utilization (CCU) to produce methanol is a beneficial pathway to use carbon dioxide (CO2 ) and mitigate climate change. Existing life cycle assessments demonstrate that CCU methanol generates a net CO2 benefit when the hydrogen (H2 ), required for hydrogenating the captured CO2, is generated by electrolyzing water using renewable electricity (RE). However, the findings do not account for the environmental opportunity cost when RE can be supplied to the grid to offset CO2 intensive electricity instead of electrolyzing water, the energy penalty of capturing CO2 and the scope for technological improvement. This study quantifies the environmental opportunity cost and determines the net CO2 emissions when CCU methanol offsets the production of conventional methanol across 14 scenarios. The 14 scenarios account for capturing CO2 from 3 sources (combined and conventional natural gas, and coal power plants) and generating H2 with electricity from 3 sources (photovoltaics, wind and the grid). The CO2 avoided by using RE on the grid is greater than that from producing CCU methanol by 660 to 11960 kg CO2 /ton methanol across the 14 scenarios. Unless the grid CO2 intensity drops below 67 g CO2 /kWh, it is environmentally preferable to supply RE to the grid than for use in CCU methanol production. At the thermodynamic limit of CCU methanol production, the grid CO2 intensity should be lower than 82 g CO2 /kWh, which is unlikely in the US before 2050.